PARTIAL PURIFICATION AND DETECTION OF HYALURONAN OLIGO BINDING PROTEIN IN HUMAN BREAST CANCER TISSUE - SRINIVAS PRASAD KOLLAPALLI; SHIB DAS BANERJEE; KARUNA KUMAR MORTHA (The Bioscan, 2012)
Hyaluronan is a versatile molecule that can form variety of periodic multimolecular structures through its interaction with specific HA binding proteins. There is increasing evidence showing, HA oligosaccharides expression was associated with malignant progression. HA-oligosaccharides have diverse and complex biological functions both In vivo and In vitro and are shown to enhance or prevent tumor growth, depending on the size of the fragment through interaction with its receptors. We produced HA 8-20 mers size fragments by enzymatic digestion of HA polymer and characterized by fluorescent assisted carbohydrate electrophoresis. Expression of hyaluronic acid binding proteins for HA polymer and HA oligosaccharides were detected by western blot analysis, which suggested that HA polymer has detected multiple receptors, while HA fragments identified mainly 80 and 66 kDa receptors with enhanced expression in malignant breast tumor, which suggested the increased specificity of HA oligosaccharides to its receptors.